2019
DOI: 10.3390/e22010053
|View full text |Cite
|
Sign up to set email alerts
|

Explanation of Experimentally Observed Phenomena in Hot Tokamak Plasmas from the Nonequilibrium Thermodynamics Position

Abstract: In studying the hot plasma behavior in tokamak devices, the classical approach for collisional processes is traditionally used. This approach leaves unexplained a number of phenomena observed in experiments related to plasma energy confinement. Further, it is well known that tokamak plasma is always turbulent and self-organized. In the present paper, we show that the nonequilibrium thermodynamics approach allows us to explain many observed dependences and paradoxes; for example, puffing of impurities results i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 24 publications
0
6
0
Order By: Relevance
“…When the input power is inconsistent with the self-consistent pressure profile, it results in a deviation of the pressure profile from the self-consistent profile and accordingly in the increase in the free energy F. The free energy increase results in the increase in the disturbed flux Γ 1 and of the coefficient κ = θ•(χ 0 + χ 1 ). The resulting flux Γ 1 aims to bring the pressure profile closer to the self-consistent pressure profile [4,16,17].…”
Section: Heat Flux For the Energy Balance Equationmentioning
confidence: 99%
See 1 more Smart Citation
“…When the input power is inconsistent with the self-consistent pressure profile, it results in a deviation of the pressure profile from the self-consistent profile and accordingly in the increase in the free energy F. The free energy increase results in the increase in the disturbed flux Γ 1 and of the coefficient κ = θ•(χ 0 + χ 1 ). The resulting flux Γ 1 aims to bring the pressure profile closer to the self-consistent pressure profile [4,16,17].…”
Section: Heat Flux For the Energy Balance Equationmentioning
confidence: 99%
“…It was shown in [3,4,16,17] that the experimentally observed self-consistent pressure profiles in a tokamak can be described within the framework of the nonequilibrium thermodynamics approach. This approach is successfully used to describe complex nonequilibrium systems in other fields of science, when the desired stable states correspond to the minimum free energy and represent the solution of the equation δF = δ(−θ•S + E) = 0, where S and E are entropy and energy respectively, and θ is some effective turbulent temperature.…”
Section: Introductionmentioning
confidence: 99%
“…When the energy deposited is inconsistent with the pressure profile, it destroys the self-consistent pressure, and leads to an increase in the free energy F, an increase in the level of turbulence and flux Γ 1 , and as a consequence, an increase in the transport coefficient κ = θ(χ 0 + χ 1 ). Here, the coefficient χ 1 depends on the value of Γ 1 , the part of the total flux Γ that smooths out the pressure profile distortion [11,12].…”
Section: Self-organization Of Plasma and The Selfconsistent Pressure ...mentioning
confidence: 99%
“…In papers [10][11][12] it was shown that in regimes without transport barriers, the conservation of the normalized pressure profile p N (ρ) in tokamaks with different heating powers can be explained within the framework of the approach of nonequilibrium thermodynamics.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation